Spontaneous rupture of the urinary bladder: can COVID predispose? - Kulkarni, Shrirang V.; Pandey, Alok K. (International Surgery Journal, 2022)
The urogenital tract is a rare source of pneumoperitoneum in peritonitis. Spontaneous rupture of the urinary bladder (SRUB) as a cause is rarer. Preceding severe acute respiratory syndrome coronavirus-2 (SARS‐CoV‐2) infection predisposing to such eventuality is unprecedented. Experience with such a singular case is presented and discussed.